The secret of the lost pearls - Wilde, Darcie (Wilde, Darcie. Useful woman mystery., 2023)
Rosalind Thorne, known among society ladies as a "most useful woman" for her discretion and connections that allow her to discover almost anything about anyone, investigates the disappearance of a valuable pearl necklace belonging to Bethany Douglas and discovers secrets swirling around the Douglas family, including fraud, forgery, blackmail, and soon, murder.